Efficacy of telbivudine and entecavir against virus reactivation in HBeAg−patients undergoing chemotherapy. Issue 22 (29th May 2020) - Chen, Chih-Jen; Yu, Hsien-Chung; Chang, Chen-Wang; Bair, Ming-Jong; Lin, Ching-Chung; Lin, Yang-Sheng; Cai, Zong-Sian; Chen, Ming-Jen
Abstract : Abstract: The renal protective effect of telbivudine (LdT) was verified by a previous meta-analysis. It was left unclear, however if this effect offsets the associated risk of virological breakthrough in hepatitis B e-antigen-negative (HBeAg−) patients receiving chemotherapy (C/T). Records of 260 HBeAg−, non-cirrhotic cancer patients undergoing systemic C/T with prophylactic LdT or entecavir (ETV) were retrospectively investigated. The investigation was conducted 6 months after completion of C/T, patient death from cancer, or antiviral modification. Treatment duration, outcome, change of renal function, and reason for antiviral modification were analyzed. The primary endpoint was the occurrence of virological breakthrough during prophylaxis C/T and the change in renal function. Of the 126 HBeAg− patients treated with LdT, 3 (2.38%) experienced HBV virological breakthroughs, whereas none of the patients treated with ETV ( P = .07) did. The estimated glomerular filtration rate for the patients treated with LdT was essentially unaltered, decreasing only slightly from 87.5 ± 23.1 to 87.3 ± 21.3 ml/minute/1.73 m 2 ( P = .55), while the rate for the ETV-treated patients was significantly lowered from 95.7 ± 32.2 to 85.5 ± 85.7 ml/minute/1.73 m 2 ( P = .0009). The absolute risk reduction ARR is 27.8% − 21.2% = 6.6%, comparing ETV with LdT for reduction of renal function impairment and the absolute risk increase for virological breakthrough during C/T, the absolute risk increase (ARI) is 2.38% − 0% = 2.38%. The overall likelihood of being helped over being harmed was 2.77. With careful selection of patients with the criteria of HBeAg−status and non-hematologic cancer, it is feasible that telbivudine raise lower probability of virological breakthroughs during prophylaxis treatment.